Tourism digital innovation geographic information system based web application for spatial information of tourism destinations - Hidayat, Amrul Rais; Khotimah, Tutik; Meimaharani, Rizkysari (Journal of Soft Computing Exploration, 2025)
This study aims to develop a web-based tourism application by utilizing Geographic Information System (GIS) to optimize the dissemination of tourism information in the Pati Karisidenan area. This application is designed to assist local communities and tourists in choosing tourist destinations by providing information such as location, description, route, facilities, and visitor reviews. In addition, the app is also equipped with search and filtering features to help users find tourist attractions based on category, distance, or available facilities. This application was developed using the PHP programming language and MySQL database. The development process adopts the Waterfall method, which consists of the requirements analysis stage, system design using ERD and DFD, implementation, testing, and maintenance. Application testing is carried out using the Black Box Testing method to ensure all functions run according to specifications. The test results from visitors showed satisfaction with the use of the application by 97% of 15 audiences. This application is expected to support the promotion, accessibility, and management of tourism potential digitally by local governments.